155k views
4 votes
Solve the system of equations. (1 point)

x + 3y = −1
2x + 2y = 6

a
(−4, 1)

b
(2, −1)

c
(4, −1)

d
(5, −2)

1 Answer

7 votes

Answer:

Answer (d): (5, -2)

Explanation:

Let's use the substitution method. Eliminate "x" in the second equation. Solving the first equation for x, we get x = -3y - 1. Subbing this for x in the second equation, we get:

2(-3y - 1) + 2y = 6, or, after multiplying as indicated,

-6y - 2 + 2y = 6.

Combining like terms,

-4y = 8, so that y = -2. If y = -2, then x is found from x = -3y - 1 (see above):

x = -3(-2) -1 = 5

Then the solution is (5, -2) (Answer d)

User Derjanb
by
6.3k points